Agricultural Potential of Polish Voivodships in the Context of Sustainable Development - Iwona Foryś; Joanna Cymerman (Barometr Regionalny)
The paper focuses on the issue of the agricultural potential of Polish voivodships in the context of sustainable development. The overall objective is to measure the potential of individual voivodship markets in 2005 and 2015 and to identify those voivodships where the development potential is the biggest, based on the changes that took place over the decade between 2005 and 2015. The authors examined the agricultural potential of individual voivodships, concentrating not only on the agricultural land resources and quality, but also on the supporting infrastructure and socio-demographic factors in the environment of this property market segment. Detailed analyses covered 7 groups of diagnostic variables: geodesic areas, agricultural land, demographic variables, population incomes, agricultural production, ecology and infrastructure. The data came from the Central Statistical Office of Poland. The authors ranked the voivodships by means of a synthetic measure which took into account the groups of variables that characterized the phenomenon under study.